Risk Factors and Management of Unexplained Limb Pain among Growing Children in a Tertiary Hospital (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Recurrent lower limb pain (growing pain) is the most common presenting problem of children referred to pediatric rheumatology clinics. The exact nature and aetiology still remains unclear despite the various hypotheses and theories presented in the international literature. Parents become apprehensive as physician are unsure regarding accurate diagnosis of unexplained limb pain.Objectives: To determine the risk factors of unexplained limb pain in growing children and measures taken for their management.Materials and Methods: This cross sectional study was conducted among 60 children of 3 to 12 years who presented with unexplained limb pains between July to December, 2012 in Paediatric OPD of Combined Military Hospital (CMH) Dhaka.Results: Mean age of the respondents was 7.4 years. Prevalence of growing pain was 75%, overweight 13.3% and obesity was 15.6%. The calf (37.3%) was the most common affected site for pain and in 68.3% and 31.7% cases pain occurred during night and evening respectively. Pain frequency was as follows: daily 8%; weekly 48%; monthly 31%; and every 3 months 13%. Growing Pain usually occur at slow growing period (80.4%) than rapid growing period (19.6%). The main therapeutic approach was massaging (84.4%) the painful limbs and to a lesser extent, the intake of oral anti-inflammatory agents (31.1%). All patients had laboratory tests within normal values.Conclusions: Growing pain (GP) is a frequent non-inflammatory syndrome that is relatively common in children and usually benign. It commonly affects the lower extremities of children. Precise history taking and physical examination makes clinical diagnosis easier. Patients’ and family eassurance is of utmost importance in management of GP.JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 59-62